Subjective Fitness and Health as Mediators of the Relationship Between Regular Physical Activity and Life Satisfaction (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Regular physical activity brings well-documented benefits for both physical and mental health. Nevertheless, many adults remain insufficiently active, increasing their risk of chronic illness and reduced wellbeing. While greater physical activity is often associated with higher life satisfaction, the mechanisms underlying this link are still not fully understood. This study investigated whether self-perceived physical fitness and general health mediate the relationship between physical activity and life satisfaction.Methods: An online survey was completed by 282 adults aged 18–72. Participants rated their fitness and general health and completed the Satisfaction with Life Scale. Based on weekly physical activity levels, respondents were classified into four categories according to World Health Organization guidelines on physical activity and sedentary behaviour. A serial mediation model was used to assess the direct and indirect effects of physical activity on life satisfaction via self-perceived fitness and health.Results: The direct effect of physical activity on life satisfaction was not significant (estimate = −0.017; 95% confidence interval (CI) = −0.161, 0.139; β = −0.014). However, a significant indirect effect emerged for the sequential path via fitness and health (estimate = 0.083; 95% CI = 0.044, 0.146; β = 0.066). Higher physical activity predicted better self-perceived fitness (estimate = 0.475; 95% CI = 0.365, 0.588; β = 0.446), which was linked to better-perceived health (estimate = 0.422; 95% CI = 0.325, 0.523; β = 0.531). Better perceived health, in turn, predicted higher life satisfaction (estimate = 0.415; 95% CI = 0.213, 0.623; β = 0.278). The indirect effects of fitness alone (estimate = 0.042; 95% CI = −0.044, 0.123; β = 0.033) and health alone (estimate = 0.012; 95% CI = −0.030, 0.061; β = 0.009) were not significant, which highlights the importance of the sequential pathway involving both mediators.Conclusion: Self-perceived fitness and health were confirmed to fully mediate the relationship between physical activity level and life satisfaction. The results suggest that the psychological benefits of an active lifestyle may depend less on objective activity levels and more on how individuals perceive their physical competence and general health. These findings underscore the potential value of addressing subjective perceptions of fitness and health in interventions that aim to promote psychological wellbeing through physical activity.